2002
DOI: 10.4269/ajtmh.2002.66.653
|View full text |Cite
|
Sign up to set email alerts
|

New emerging Plasmodium falciparum genotypes in children during the transition phase from asymptomatic parasitemia to malaria.

Abstract: Abstract. Semi-immunity against Plasmodium falciparum occurs after many infections. In areas of high malaria transmission, the prevalence of asymptomatic parasite carriers increases with age. We investigated P. falciparum genotypes in a cohort of asymptomatic carriers who were followed until they became symptomatic. Blood spots on filter paper and blood smears were collected daily from 10 children in Lambaréné, Gabon. The parasite genotypes present on successive days were determined by a polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 17 publications
6
40
1
3
Order By: Relevance
“…Magesa and coworkers reported similar results, with daily changes in both parasite density and genotypic pattern (Magesa et al 2002). However, in another study by our group, we demonstrated the unchanging pattern of parasites over time during the asymptomatic phase of infection, with the appearance of a new genotype coinciding with clinical symptoms (Kun et al 2002). These studies (Fa¨rnert et al 1997;Magesa et al 2002;Kun et al 2002), which were investigating untreated infections, are fundamentally different from the present study, which follows patients undergoing quinine treatment.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Magesa and coworkers reported similar results, with daily changes in both parasite density and genotypic pattern (Magesa et al 2002). However, in another study by our group, we demonstrated the unchanging pattern of parasites over time during the asymptomatic phase of infection, with the appearance of a new genotype coinciding with clinical symptoms (Kun et al 2002). These studies (Fa¨rnert et al 1997;Magesa et al 2002;Kun et al 2002), which were investigating untreated infections, are fundamentally different from the present study, which follows patients undergoing quinine treatment.…”
Section: Discussionsupporting
confidence: 48%
“…The genetic composition of the parasites in an individual throughout the course of infection was not well known, because most studies were cross-sectional surveys of parasites in the blood of infected people at a single time-point. Nevertheless, longitudinal studies on asymptomatic children in eastern Africa showed a daily variation in the P. falciparum population (Fa¨rnert et al 1997) while, in Gabonese children, there was a constant parasite profile throughout an asymptomatic infection (Kun et al 2002). In patients with falciparum malaria, studies on the genetic characteristics of the parasite are so far limited to the association between parasite genotype and disease severity (Robert et al 1996;Kun et al 1998) or the association between the complexity of the infection and susceptibility to malaria (Fa¨rnert et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that reinfection with new clones (to which the individual had not previously been exposed) could trigger an increase in parasite density and the development of symptoms [56], but other studies have demonstrated that symptoms can appear without any change in clonal diversity [55].…”
Section: Do Asymptomatic Blood-stage Infections Eventually Become Symmentioning
confidence: 99%
“…It was believed that longterm asymptomatic carriage may represent a form of tolerance to the parasite in adults as well as children, building up their immune response, thereby protecting them from developing either a mild malarial attack or a more severe one by keeping their immunity effective. 3 On the other hand, asymptomatic carriage may represent a mode of entry to symptomatic malaria, as well as transmission, especially in young children. 4,5 Malaria is a major public health problem in Ethiopia, where ~68% of the population lives in malaria-risk areas.…”
Section: Introductionmentioning
confidence: 99%